Bone Density and Structure in Overweight Men With and Without Diabetes - Starup-Linde, Jakob; Ornstrup, Marie Juul; Kjær, Thomas Nordstrøm; Lykkeboe, Simon; Handberg, Aase; Gregersen, Søren; Harsløf, Torben; Pedersen, Steen Bønløkke; Vestergaard, Peter; Langdahl, Bente Lomholt (Frontiers in Endocrinology, 2022)
Objective: Metabolic syndrome (MetS), type 1 diabetes (T1D), and type 2 diabetes, are associated with an increased risk of fractures; however, the impact of obesity on bone deficits in diabetes is unknown. We aimed to compare markers of bone structure, bone density, and bone turnover in non-diabetic overweight males with MetS and overweight males with T1D or T2D. Methods and research design: In this cross-sectional study we included participants from two previously described study cohorts consisting of participants with diabetes and participants with MetS. Participants underwent dual-energy X-ray absorptiometry measuring areal bone mineral density (aBMD) at the hip and lumbar spine, High Resolution peripheral Quantitative (HRpQCT) scan of the tibia and radius and measurement of circulating bone turnover markers. We compared groups with unpaired t test and performed multiple linear regression with adjustment for age, body mass index, and smoking. Results: We included 33 participants with T1D, 25 participants with T2D, and 34 participants with MetS. Bone turnover markers levels were comparable between T1D and MetS. aBMD at the hip was lower in T1D compared to MetS, also after adjustment. P1NP and Osteocalcin levels were lower among individuals with T2D compared to MetS, whereas aBMD were similar between the groups after multiple adjustment. We observed no difference in volumetric BMD at the tibia or radius between MetS and T1D and T2D, respectively. Participants with T2D had a higher trabecular number and lower trabecular separation compared to individuals with MetS at the tibia, which remained signficant after multiple adjustment. Conclusion: In conclusion, we observed no clinically important differences in bone density or structure between males with T2D, T1D, or MetS. However, males with T2D displayed lower bone turnover compared to MetS highlighting that T2D per se and not obesity, is associated with low bone turnover.